What Difference Do the New WHO Child Growth Standards Make for the Prevalence and Socioeconomic Distribution of Undernutrition? - Ergo, A. (2012)
BACKGROUND: The World Health Organization has recently established revised child growth standards. OBJECTIVE: To assess how the use of these new standards affects the estimated prevalence and socioeconomic distribution of stunting and underweight among children in a large number of low- and middle-income countries. METHODS: We analyzed Demographic and Health Survey data for stunting and underweight in 41 low- and middle-income countries employing these new standards and compared the results with those produced by analyses of the same data using the old growth references. RESULTS: For all 41 countries, the prevalence of stunting increases with the adoption of the new standards, by 5.4 percentage points on average (95% CI: 5.1, 5.7). The prevalence of underweight decreases in all but two of the countries, by an average of 2.9 percentage points (95% CI: 2.7, 3.2). The impact of using the new standards on socioeconomic inequalities is mixed. For stunting, inequalities tend to rise in absolute terms but tend to decline in relative terms. The impact on underweight is inconsistent across countries. Poor children suffer most from undernutrition, but even among the better-off children in developing countries, undernutrition rates are high enough to deserve attention. CONCLUSIONS: These results suggest that the adoption of the new WHO standards in itself is unlikely to affect policies dramatically. They do confirm, however, that different strategies are likely to be required in these countries to effectively address undernutrition among children at different socioeconomic levels.